Performance Investigation of a Solar Heat Driven Adsorption Chiller under Two Different Climatic Conditions - Choudhury, B. (Springer India, 2018)
The demand for cooling, especially in the developing economies, is rising at a fast rate. Fast-depleting sources of fossil fuel and environmental concerns necessitate looking for alternative cooling solutions. Solar heat driven adsorption based cooling cycles are environmentally friendly due to their use of natural refrigerants and the thermal compression process. In this paper, a performance simulation study of a basic two-bed solar adsorption chiller has been performed through a transient model for two different climatic locations in India. Effect of operating temperatures and cycle time on the chiller performance has been studied. It is observed that the solar hot water temperature obtained in the composite climate of Delhi (28.65°N, 77.25°E) can run the basic adsorption cooling cycle efficiently throughout the year. Whereas, the monsoon months of July and August in the warm and humid climate of Durgapur (23.48°N, 87.32°E) are unable to supply the required driving heat. © 2017, The Institution of Engineers (India).